Teacher Motivation, Preventive Strategies toward Lesson Implementation in Physical Education Teachers - Khun-inkeeree, Hareesol; Tulyakul, Singha (Technium Social Sciences Journal, 2021)
The main influence on physical education (PE) teachers is motivation involves the methods of preventing misbehavior. The respondents comprise the teacher who are teach PE classes in primary school at Southern Thailand amount 298 teachers. The instrument includes three questionnaires namely; The Autonomous Motivation for Teaching Questionnaire (AMTQ) was employed to collect data in terms of teacher motivation, in part of lesson implementation used the Self-Evaluation of Teacher Effectiveness Questionnaire in Physical Education (SETEQ-PE) to collect data, and classroom management strategies questionnaire was employed for collect data in preventive strategies aspect. There are two statistical software utilized for analysis data, namely; Statistical Package for Social Sciences (SPSS) version 23 used for preliminary data analysis. While, the Partial Least Square- Structural Equation Modeling (PLS-SEM) version 3 used for analytical the structural equation model. The finding found that there is a significant relationship between intrinsic motivation, preventive strategies, and lesson implementation. Meanwhile, there is no significant relationship between external motivation toward preventive strategies and lesson implementation among primary school teachers in Southern Thailand. The implication of this result as an evident empirical study to assist the importance of teacher motivation and lesson implementation and contributed the teacher to enhance motivation for teaching to improve the higher effective PE instruction.